DICHTOTOMY OF IMPROVING THE QUALITY OF WOMEN'S HUMAN RESOURCES IN IMPROVING FOOD SECURITY - Suparmono Suparmono (FE Program Studi Manajemen, 2026)
The food crisis, which is predicted to hit most countries, needs to be anticipated through appropriate policies. This study aims to analyze the dichotomy of the influence of improving the quality of women's human resources, as proxied by the Gender Empowerment Index, poverty, and the Human Development Index (HDI), on food security between cities and regencies in the Special Region of Yogyakarta.Using a quantitative approach using panel data from five regencies/cities for 2018-2024, it was found that gender empowerment has a significant impact on food security. Poverty and the Human Development Index do not significantly influence food security. This finding is consistent with previous research, allowing for the development of strategies to improve food security in the Special Region of Yogyakarta. Food security policies are evenly distributed, indicating no differences between cities and regencies in food security policies